2020
DOI: 10.1097/sla.0000000000004586
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acquiring Perioperative COVID-19 During the Initial Pandemic Peak: A Retrospective Cohort Study

Abstract: Objective: To determine the risk of acquiring perioperative COVID-19 infection in previously COVID-19 negative patients. Summary of Background Data: During the initial peak of the COVID-19 pandemic, there was significant concern of hospital acquired COVID-19 infections. Medical centers rapidly implemented systems to minimize perioperative transmission, including routine preoperative testing, patient isolation, and enhanced cleaning. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“… 19 Axiotakis et al also reported zero cases of COVID‐19 among 170 patients undergoing preoperative RT‐PCR testing preoperatively. 20 Specifically looking at studies including patients undergoing head and neck surgery, our results are also in line with a study of 47 head and neck patients in the United Kingdom in which there were no cases of COVID‐19 diagnosed. 21 …”
Section: Discussionsupporting
confidence: 88%
“… 19 Axiotakis et al also reported zero cases of COVID‐19 among 170 patients undergoing preoperative RT‐PCR testing preoperatively. 20 Specifically looking at studies including patients undergoing head and neck surgery, our results are also in line with a study of 47 head and neck patients in the United Kingdom in which there were no cases of COVID‐19 diagnosed. 21 …”
Section: Discussionsupporting
confidence: 88%
“… 36 In our study, 77.5% of our respondents did not care or were neutral about the no-visitor policy implemented at our institution. These data are comparable to those in a Howard et al 18 study that showed 84.2% of patients undergoing elective orthopedic surgery were willing to comply with strict self-isolation for 2 weeks before and after the procedure and understood the no-visitor policy when it was explained. These results again demonstrate the willingness of patients to comply with precautions when they are adequately educated on the rationale.…”
Section: Discussionsupporting
confidence: 85%
“…25 , 26 , 27 This has likely discouraged these populations from seeking medical care, as hospitals are viewed to be COVID-19 hot spots. 18 However, recent data suggest that the implementation of preoperative COVID-19 screening and self-quarantining for elective orthopedic surgery has not been associated with any cases of COVID-19 as confirmed by polymerase chain reaction testing. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient healed from the infection in a month and continued the oncological follow-up. Our COVID-19 infection rate was slightly lower than that shown in a previous report [ 18 ]. Reasons underlying this result are hypothetical and include an early implementation of routine preoperative testing for all the patients and subdivision of admitted patients in different wards.…”
Section: Discussioncontrasting
confidence: 83%